(untitled) (Research, Society and Development, 2021)
The research aimed to analyze the main causes of socio-occupational illness of the Social Worker. Where the study is a qualitative research that used a bibliographic analysis of a narrative character, which was carried out by consulting online research databases, namely: Scielo (Scientific Electronic Library OnLine), VHL (Virtual Health Library), and academic Google. The current context demands too much from professionals and often puts them at risk of illness. Where continuing education helps professionals to think of effective responses for their protection to multiple expressions of the social issue, such training should be a duty of the state to improve public service. It should also be noted that the role of social workers can include any of the stages of a person’s life. In this aspect, during mourning, the professional can look for ways to help the individual to live the experience without compromising their life permanently. When the worker gets sick, it doesn’t only affect him, there is a network of people affected by a sick worker where it can be said that it is the family, as it lives daily with the worker. Finally, the study allowed to deepen the knowledge about workers’ health, social assistance and the factors that influence the illness of professionals working in the area. It is expected that more research will be carried out in this line of investigation in order to prove the importance of these professionals and the need to provide assistance to their physical and psychological health.